An inverse problem of determining the time-dependent potential in a higher-order Boussinesq-Love equation from boundary data. Issue 10 (21st May 2021) - Huntul, M.J.; Tamsir, Mohammad; Ahmadini, Abdullah
Abstract : Purpose: The paper aims to numerically solve the inverse problem of determining the time-dependent potential coefficient along with the temperature in a higher-order Boussinesq-Love equation (BLE) with initial and Neumann boundary conditions supplemented by boundary data, for the first time. Design/methodology/approach: From the literature, the authors already know that this inverse problem has a unique solution. However, the problem is still ill-posed by being unstable to noise in the input data. For the numerical realization, the authors apply the generalized finite difference method (GFDM) for solving the BLE along with the Tikhonov regularization to find stable and accurate numerical solutions. The regularized nonlinear minimization is performed using the MATLAB subroutine lsqnonlin . The stability analysis of solution of the BLE is proved using the von Neumann method. Findings: The present numerical results demonstrate that obtained solutions are stable and accurate. Practical implications: Since noisy data are inverted, the study models real situations in which practical measurements are inherently contaminated with noise. Originality/value: The knowledge of this physical property coefficient is very important in various areas of human activity such as seismology, mineral exploration, biology, medicine, quality control of industrial products, etc. The originality lies in the insight gained by performing the numerical simulations of inversion to find the potential co-efficient on time in the BLE from noisy measurement.